Comparison of Automatically Controlled Injection System with a Traditional. Syringe for Multiple Infiltrations in Children Aged 6-12 Years: A Randomized Controlled Trial - Beegum Fahanna; Elshaboury Shaimaa N; Alghofaili Abeer I; Habibullah Mohammed A; Karthika S (Wolters Kluwer Medknow Publications, 2024)
Children's conduct is significantly impacted by pain during dental procedures. Children's pain and discomfort can be reduced using computer-controlled local anesthetic delivery, which applies a steady, gradual flow of the anesthetic solution into the tissues. Using a self-report anxiety scale, the study aimed to assess and compare children's perceptions of discomfort following a new auto-controlled injection method to a traditional local anesthetic procedure. A total of 25 children, ages 6-12 requiring the use of local anesthesia for treatment on both sides of the arch were selected. It was a split-mouth design, in which each participating child received both types of infiltrations in two separate, consecutive visits, using a metallic syringe in one session, and using the I-Ject device in the other. Before administering anesthesia, all the children's anxiety scales were recorded using the Modified Child Dental Anxiety Faces Scale simplified to assess the anxiety level of a child. In the first appointment, Conventional anesthetic technique was and in the second appointment anesthesia was delivered using a computer-controlled device. Faces pain scaleRevised, a selfreport measure of pain was recorded immediately after completion of both types of local anesthesia (LA) administration. Patients reported greater comfort with the I-Ject computer-controlled device than with conventional anesthesia. Together with the practitioner, the computer system produced a pleasant and cozy environment for the youngster.